Structural Change in Argentina, 1935–1960: The Role of Import Substitution and Factor Endowments - Dario Debowicz (The Journal of Economic History, 2014)
This paper investigates structural change in Argentina from 1935 to 1960, a period of rapid industrialisation and relative decline of agriculture. The paper argues that the main driver of the relative decline of agriculture is the closing of the land frontier and the associated change in factor endowments as the population continued to grow.